The Pedagogical Essence And Content Of The Problem Of Developing Students’ Educational Competencies In Digital Culture And Information Security (Journal of Pedagogical Inventions and Practices, 2026)
The article examines the pedagogical essence and content of developing students’ educational competencies in digital culture and information security within the context of the digital transformation of education. It analyzes the theoretical foundations of digital culture, media and information literacy, cybersecurity awareness, and responsible digital citizenship. Particular attention is paid to competence-based, learner-centered, and activity-oriented approaches that facilitate the formation of students’ digital knowledge, skills, values, and ethical behavior. The study also highlights the role of educational institutions in fostering a safe digital learning environment through innovative pedagogical methods and digital technologies. The findings emphasize that the development of digital culture and information security competencies contributes to students’ critical thinking, responsible online behavior, and lifelong learning in the information society